Dowry System: Destruction of Economic, Social and Moral Values: Understanding the Impact of Dowry System on Economic, Social, and Moral Values during Recession (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Most of us in the western world would shudder at the newsof economic recession. Recession means the economy is not doing well, andpeople are going to be laid out or loose their jobs. In simpler term, recessionmeans that the people are not spending enough outside their homes. Its onlywhen people spend out side their homes, the economy of any society or countrymoves forward.